2020
DOI: 10.1021/acs.joc.0c00982
|View full text |Cite
|
Sign up to set email alerts
|

Serendipitous Synthesis of Pyridoquinazolinones via an Oxidative C–C Bond Cleavage

Abstract: A direct one-pot copper-catalyzed oxidative C–C bond cleavage route to the synthesis of pyridoquinazolinones is described. This one-pot strategy involves a copper-catalyzed C–N coupling followed by concomitant C­(sp3)–H oxidation and amidation via oxidative C–C bond cleavage under an O2 atmosphere to deliver the target molecules in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 79 publications
1
8
0
1
Order By: Relevance
“…Based on the results of previous studies, [10,12] a plausible mechanism was proposed as shown in scheme 2. An Ullmann-Goldberg typed C-N coupling would firstly afford the N-pyridyl substituted 2'-aminoacetophenone 4, which was oxidized to furnish the glyoxalic-typed intermediate 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results of previous studies, [10,12] a plausible mechanism was proposed as shown in scheme 2. An Ullmann-Goldberg typed C-N coupling would firstly afford the N-pyridyl substituted 2'-aminoacetophenone 4, which was oxidized to furnish the glyoxalic-typed intermediate 5.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained species would undergo a sequence of cyclization/decarboxylation to yield the targeted pyrido-fused quinazolinone 3aa. [12] An alternative pathway would comprise the Cu/TEMPO comediated, partial oxidation of 4 to afford the phenylgloxal-typed intermediate 6. Nucleophilic addition followed by oxidation would furnish the N-…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), Cu(acac) 2 (1 mol%) and Pybox (1.2 mol%) in MeOH at room temperature for 6 h. When compared with the A 3 -coupling reaction, the formation of intermediate 64 via propargylation of 2-aminopyridines at the pyridine-nitrogen with compound 62 was proposed as the initial step in a cascade reaction. Kaliappan et al [52] reported a direct synthesis of pyridoquinazolinone (66) from 2-aminopyridine (1 a, 1.2 equiv.) and 2-iodoacetophenone (65, 1.0 equiv.)…”
Section: Metal-catalyzed Reactionsmentioning
confidence: 99%
“…其中, 基于邻卤 苯乙酮的合成最常见 [99] . 例如, Kaliappan 课题组 [100] 最 近报道, 邻溴苯乙酮与 2-氨基吡啶 1 反应, 经 Ullmann-Goldberg 型偶联反应、铜(I)催化氧化加成、还原消除、 分子内成环、甲基被氧化为 CO 2 离去的历程, 生成吡啶 喹唑啉酮(Eq. 16).…”
Section: 以多官能团酯类为原料unclassified